2010 4th International Conference on Bioinformatics and Biomedical Engineering 2010
DOI: 10.1109/icbbe.2010.5516985
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and Nitrite Pollution in the Jiantan River in the Three Gorges Reservoir Area

Abstract: EC value, pH value, pE value, nitrate nitrogen and nitrite nitrogen of surface water and groundwater in the Jiantan River in the Three Gorges Reservoir Area were measured and analyzed to depict the spatial distribution of nitrate and nitrite pollution in the study basin. The results show the nitrate nitrogen level of the groundwater in the study basin is holistically larger than those of the surface water, and nitrate nitrogen level of the surface water in the study basin reveals a gradually elevatory tendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…As discussed in Section 3.1, NO 3 – –N was the major component of DIN and TDN, with its concentration significantly exceeding that of the natural background (0.08–0.12 mg/L), suggesting the presence of additional N input sources. Previous studies have shown that the industries’ wastewater exhibits higher NO 3 – –N and lower Cl – , which is reversed in the cropland . As depicted in Figure b, the NO 3 – –N/Cl – values of the YL samples were closer to the end-member of agricultural activities, whereas the CQ and FW samples displayed a stronger association with urban activities.…”
Section: Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As discussed in Section 3.1, NO 3 – –N was the major component of DIN and TDN, with its concentration significantly exceeding that of the natural background (0.08–0.12 mg/L), suggesting the presence of additional N input sources. Previous studies have shown that the industries’ wastewater exhibits higher NO 3 – –N and lower Cl – , which is reversed in the cropland . As depicted in Figure b, the NO 3 – –N/Cl – values of the YL samples were closer to the end-member of agricultural activities, whereas the CQ and FW samples displayed a stronger association with urban activities.…”
Section: Results and Discussionmentioning
confidence: 92%
“…(b) Response of the ratio of NO 3− −N/ Cl − to different anthropogenic sources. The data of urban and agriculture end-member were according to Liu et al59 and Li et al,60 respectively.…”
mentioning
confidence: 99%
“…These species occur widely in wastewater and surface waters. Besides, the concentration of NO 2 – in surface waters at the downstream ranges from 0.174 to 0.181 mg-N/L, and up to 1 mg-N/L can be found in surface waters with agriculture runoff. NO 2 – is also ubiquitous in biologically treated wastewaters where it forms due to incomplete nitrification/denitrification, with the concentration at mg-N/L level or lower. , Thus, this study addresses an overlooked photochemical pathway that can lead to the formation of NDMA in sunlit surface waters, especially those receiving WWTP effluents.…”
Section: Introductionmentioning
confidence: 98%
“…Liangtan River is one of the main tributaries from the right bank of Jialing River downstream with a total length of 88km, with average annual flow of 6.6m 3 /s. In recent years, Liangtan River is polluted seriously: the water quality is worse than Class V and belongs to heavy pollution [8]. Besides of livestock and domestic pollution, the quality deterioration of the Liangtan River is mainly attributable to the sediment pollution in the river and its pollution load accounts for 10% of overall pollution.…”
Section: Introductionmentioning
confidence: 99%